PENGARUH LITERASI KEUANGAN, PERENCANAAN KEUANGAN DAN PENDAPATAN TERHADAP KESEJAHTERAAN KEUANGAN GURU PEREMPUAN DI KOTA DENPASAR - Hidayah, Anisa Putri Nur; Purbawangsa, Ida Bagus Anom; Abundanti, Nyoman (E-Jurnal Manajemen; Vol 10 No 7 (2021), 2021)
Financial literacy is financial knowledge and capability that affects efforts to improve financial well-being. This study aims to obtain empirical evidence that financial literacy, financial planning, and income have an effect on financial well-being. The data used in the research is primary data which was collected by conducting a survey in the form of distributing questionnaires and interviews with female teachers in Denpasar City. The sample is determined by the nonprobability sampling technique, quota sampling type. This study uses data analysis techniques Structural Equation Model (SEM) with Partial Least Square (PLS) software. This study shows that financial literacy, financial planning, and income have a positive and significant effect on the financial welfare of female teachers in Denpasar City. The implications of the theoretical research results add to the reference to empirical research on the concept of financial literacy and welfare theory. This shows that financial literacy which includes the knowledge, skills, and beliefs of individuals in managing their finances will influence financial decisions that will be made to achieve the expected financial well-being. Keywords : Financial Literacy, Planning, Income, Welfare.